2020
DOI: 10.22555/joeed.v7i1.2642
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of EFL Classroom Management Strategies employed by Public and Private School English Teachers

Abstract: <div><p>This research project was a comparative study of classroom management practices of English language teachers in secondary level public and private sector schools of Lahore. The purpose of the research was to establish the practices and the strategies used by the English language teachers. A total of 200 including 100 public sector and 100 private sector school teachers, teaching English language, were randomly selected for the present research using random sampling techniques. A clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This research identified five objectives that will guide my classroom management strategy: establishing relationships with each student, establishing relationships with parents, providing a safe environment, establishing an engaging curriculum, and establishing a proactive discipline plan. In addition, Abdullah (2020) found that the four most important classroom management strategies are regulating classroom behavior, employing specific teaching strategies, planning and providing support, and collaborating with parents.…”
Section: Classroom Management During In-person Classesmentioning
confidence: 99%
“…This research identified five objectives that will guide my classroom management strategy: establishing relationships with each student, establishing relationships with parents, providing a safe environment, establishing an engaging curriculum, and establishing a proactive discipline plan. In addition, Abdullah (2020) found that the four most important classroom management strategies are regulating classroom behavior, employing specific teaching strategies, planning and providing support, and collaborating with parents.…”
Section: Classroom Management During In-person Classesmentioning
confidence: 99%
“…Hence, effective classroom management strategies involve teachers being prepared for lessons, motivating learners, providing proper and effective discipline, making learners feel comfortable, building learners' self-esteem, and designing constructive and entertaining lesson plans (Williams & Williams, 2011, p. 2). These skills are adopted by the teacher while in the classroom (Abdullah, 2020) to ensure outcomes that are motivating (Petre, 2022).…”
Section: Classroom Management and Communication Skillsmentioning
confidence: 99%